2016
DOI: 10.1016/j.conctc.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin in chronic obstructive pulmonary disease: Results of a pilot, randomized, placebo-controlled clinical trial

Abstract: IntroductionStatins may have pleiotropic effects in COPD, but mechanisms remain unclear.ObjectivesTo assess the pleiotropic effect of statins in patients with stable COPD on (1): lung function (2); pulmonary and systemic inflammation (3); endothelial function (vascular stiffness) and circulating vascular growth factors; and (4), serum uric acid levels.MethodPilot, double-blind, randomized, placebo-controlled clinical trial in 24 patients with stable COPD, all statin-naïve, who were randomized (1:1) to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“… 12 Another two randomized controlled trials pointed out statins did not improve in pulmonary function. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Another two randomized controlled trials pointed out statins did not improve in pulmonary function. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…12 Another two randomized controlled trials pointed out statins did not improve in pulmonary function. 16,17 Some of the studies demonstrated that statins are particularly effective in COPD patients with cardiovascular comorbidity. 2,9,18 There is no doubt that COPD and cardiovascular comorbidity are often co-existed, especially more severe severity of COPD.…”
mentioning
confidence: 99%
“…Statins were postulated as possible treatment for inflammatory lung diseases including COPD. However, clinical trials like STATCOPE were shown to have an overall insignificant impact on patient outcomes [21,112,113]. Previous studies have looked at whether the reason behind the statins' inability to significantly reduce inflammation during pulmonary exacerbation is linked with ABCA1 being downregulated as a result of statin treatment [1,4,37].…”
Section: Abca1 As An Alternative Biological Target For the Treatmentmentioning
confidence: 99%
“…Ultimately, 10 of the 20 studies were selected 4-5, 11, 14-20 ; of those not included, three were excluded because they did not use a placebo control [21][22][23] , three because they used the same dataset as another study included in this meta-analysis [24][25][26] , one because it was a post-hoc analysis of a large statin-heart failure RCT 27 , one because one-quarter of the recruited patients did not complete the study 28 , one because most of the patients did not fulfil GOLD criteria for COPD 29 , and one because no outcomes of interest were reported 30 . All the included trials were published as peer-reviewed articles, and all of them were in English.…”
Section: Study Descriptionmentioning
confidence: 99%